Literature Study: Types of Social Support in Adolescents with Unwanted Pregnancy - Sifva Fauziah; Ermiati Ermiati; Eka Afrima Sari (Journal of Nursing Science Update (JNSU), 2021)
Unwanted Pregnancy in adolescents can create a negative impact on adolescents who experience it. Management of Unwanted Pregnancy by providing social support are needed to reduce the perceived impact. The limited articles on the types of social support for adolescents experiencing Unwanted Pregnancy made this literature study aimed to find out the types of social support that can be provided to adolescents who experience Unwanted Pregnancy. This research method was scoping review using search engines such as EBSCOHost, Google Scholar, and PubMed. The keywords used were "adolescents" OR "teenagers" OR "young adults" OR "student" AND "unwanted pregnancy" AND "social support". The result of article search based on inclusion and exclusion criteria had found 6 articles. Critical appraisal was done using a JBI critical appraisal checklist with a result of 6 selected articles which stated as eligible sources to be used as source of references in this literature study. The result of the review of 6 articles with content analysis found that there were 10 types of social support that can be provided to adolescents who experience Unwanted Pregnancy. The types of social support were providing information, counseling, communication, emotional support, financial support, assistance, accountability, appreciation, providing shelter and providing educational facilities. Recommendations for further research are expected to do a further analysis on types of social support that has been found, so that it can be implemented to reduce the impact on adolescents with Unwanted Pregnancy.